Stochastic modeling of concentration partitioning of charged colloids between concentrated bulk solution and narrow pores - Chun, MS; Hwang, JY; Kim, JJ (SOC CHEMICAL ENG JAPAN, 2000)
Even though purely steric partitioning within well-defined pores was treated, analytical approximations based on perturbed approach have been proved to be unreliable predictions of concentrated colloids for the whole range of relative pore size from wide to narrow, In this study, simulation results from Gibbs ensemble Monte Carlo method on electrostatic partitioning of concentrated colloids have been addressed for a cylindrical pore. The concentration profiles representing the effects of solute concentration as well as solution ionic strength are obtained via a stochastic process, and compared with the results of virial expansion. In order to determine the respective electrostatic energies between the solute and the pore wall, and between pairs of solutes, we employ previous analyses such as a solution with series representation and a singularity method. Electrostatic partitioning shows a clear dependence on solute concentration as well as ionic strength. Consistent effects of solute concentration including ionic strength are explicitly estimated by comparing the configurational order of restriction. Remarkably, our simulations reveal a possible occurrence of physical adsorption inside narrow pores, of which the partition coefficient exceeds one in the system of charged solutes and uncharged pore wall with higher solute concentration. The hindered diffusion coefficient for the dilute limit of charged system is predicted to decrease with decreasing solution ionic strength for a given pore size.
Keywords: MONTE-CARLO SIMULATION; GIBBS ENSEMBLE; PHASE-EQUILIBRIA; CYLINDRICAL PORES; POROUS-MEDIA; MOLECULES; TRANSPORT; MEMBRANES; LIQUID